Rancang Bangun Sistem Informasi Helpdesk IT Support Berbasis Website - Yosua Liharja; Ani Oktarini Sari; Arief Satriansyah (Infotek: Jurnal Informatika dan Teknologi, 2022)
The speed of providing services from the IT support department in helping to handle problems related to computer devices or internet or intranet networks in a company is very important in supporting work effectiveness. PT Markindo Rekateknik is a company engaged in marking machines, coding printers and packaging machines. Handling requests for network access or repairing computer equipment is still done manually and this process takes a long time because it needs to get approval from the leadership. This of course can cause problems in the form of missing data reports, difficulty in searching data, and the risk of data loss. And in terms of monitoring access requests and computer and network equipment problems that are often complained of in 1 month, they are not recorded properly, making it difficult for the evaluation process of these obstacles. For this reason, we need a helpdesk system for the IT Support section that is computerized and can be accessed anywhere with an internet connection, so that existing problems can be resolved properly. And the process of monitoring and reporting on access requests and computer and network equipment constraints from submitted complaints can be monitored properly and can be evaluated to find the right solution